2015
DOI: 10.2147/ijgm.s73673
|View full text |Cite
|
Sign up to set email alerts
|

A review of the pharmacoeconomics of eletriptan for the acute treatment of migraine

Abstract: Migraine is a commonly occurring, chronic disorder that can cause significant disability. Eletriptan, a selective serotonin 5-hydroxytryptamine 1 receptor subtype B/D (5-HT1B/1D) agonist, is a clinically effective treatment for moderate to severe migraine. The objective of this literature review was to summarize the available data on the pharmacoeconomics of eletriptan relative to other triptans. Articles meeting the following three criteria were included in the review: 1) contained pharmacoeconomic data on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Further, given that nearly 1/5 of households in the United States reported a layoff or reduction in work hours related to coronavirus by March 14, 2020, 3 it is imperative that insurance providers minimize or eliminate copays for migraine medications. While it may seem unthinkable to ask insurers to pay additional money for these therapies as other health care costs increase, multiple pharmacoeconomic studies have demonstrated that coverage of expensive migraine medications is actually cost‐saving, as it decreases disability and reliance on hospital care 4‐6 …”
Section: Introductionmentioning
confidence: 99%
“…Further, given that nearly 1/5 of households in the United States reported a layoff or reduction in work hours related to coronavirus by March 14, 2020, 3 it is imperative that insurance providers minimize or eliminate copays for migraine medications. While it may seem unthinkable to ask insurers to pay additional money for these therapies as other health care costs increase, multiple pharmacoeconomic studies have demonstrated that coverage of expensive migraine medications is actually cost‐saving, as it decreases disability and reliance on hospital care 4‐6 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent multiple-attacks study, eletriptan 40 and 80 mg were significantly more effective in achieving a 2-hour headache response than placebo (response rate: 72.5% for eletriptan 40 mg, 70% for eletriptan 80 mg and about 23% for placebo) with a low adverse-event rate for both doses Marmura et al 2015]. Compared with all the marketed triptans, eletriptan was found to be among the most effective in two meta-analytic studies of published placebo-controlled trials [Bhambri et al 2015]. In a meta-analysis of 53 trials, rizatriptan 10 mg, eletriptan 80 mg and almotriptan 12.5 mg showed the highest probability of a significant clinical therapeutical effect [Ferrari et al 2001].…”
Section: Eletriptan: Efficacy Versus Placebomentioning
confidence: 94%
“…Eletriptan is commercially available at doses of 40 mg or 80 mg, and has been demonstrated to be effective nearly 30 minutes after the administration. In comparative clinical trials (discussed below) eletriptan (40 and 80 mg) showed superior or equivalent efficacy to other triptans with high safety and tolerability [McCormack et al 2006], and the most favorable cost effectiveness when compared with other drugs in its class [Sandrini et al 2009;Bhambri et al 2015].…”
Section: Eletriptan Biochemical and Pharmacological Featuresmentioning
confidence: 99%
See 2 more Smart Citations